Balkan Babel : the Disintegration Of Yugoslavia From The Death Of Tito To The Fall Of Milosevic. - Ramet, Sabrina Petra (ACLS Humanities E-Book., 2002)
Yugoslavia's would-be system-builders failed three times over to build a workable system. The underlying problem was their failure to resolve the problem of legitimacy. In the 1980s, economic deterioration pushed people to despair and, under the pressure of Serbia's ambitious political establishment, the country broke up along ethnic fault lines. This volume, now in its fourth expanded edition, tells the story of socialist Yugoslavia's troubles and the challenges facing its successor states from May 1980 to July 2001.